Do Managers Use the Available Non-Committed Financial Resources at Their Discretion in Response to Stakeholder Pressure? - Braune, Eric; Hikkerova, Lubica; Boncori, Anne-Laure (Management international / International Management / Gestiòn Internacional, 2021)
We propose to explore the research question of whether managers use available non-committed financial resources at their discretion to respond to stakeholder pressure. To address this question, we investigate the relationship between the corporate social performance (CSP) of industrial companies listed on Standard & Poor’s 500 and the financial resources (financial slack) at the discretion of their managers. We find that managers can use financial slack to extend and intensify the CSP of their companies. In terms of types of CSP, these resources are not allocated to reduce the impacts of their companies’ activities on the environment. They are rather oriented toward addressing social issues and social conditions. Moreover, we find that management decisions concerning the allocation of slack resources toward an increase in CSP vary according to a company’s risk profile.